A Discourse Map on Counseling International Students in Korea - Kim, Youngsoon; Oh, Youngsub (Humanities Today: Proceedings, 2023)
The number of international students has drastically increased over a decade in Korea. And a psychological demand to make them successfully adjust their college life in Korea has also increased. Accordingly, it is necessary to explore how international student-focused counseling research has unfolded in Korea. To this end, this study provides research trend in Korea through a content analysis of 79 theses and articles published over recent two decades (1996-2016). Over 140 research contents are classified into 10 categories, including cultural adjustment, psychological health, and career and vocation as the main three categories. Frequency of conceptions or terms in each category, and relationship between those conceptions are analyzed. Based on the content analysis, a discourse map is finally drawn. Also, future research agendas are suggested.